The socioeconomic impact of inherited retinal dystrophies (IRDs) in Belgium: A cost-of-illness study - Ine Vandersmissen; Janice Geers; Tom Denee; Salla Oinasmaa; Dagmar Hoeben; Xinyi Zhang; Burcak Aydin; Simone Cheung; Lorenzo Billiet; Inge Joniau; Avril Daly; Steven Simoens; et al. (PLoS ONE, 2026)
Introduction Inherited retinal diseases (IRDs) are a diverse group of vision-threatening conditions caused by genetic mutations, affecting over 5.5 million people globally. These diseases have profound impact on patients, families and society. However, there is a lack of comprehensive data on their prevalence, economic burden, and societal costs. This information gap hinders effective decision-making, and the allocation of resources needed for research, treatment, and patient support, ultimately compromising care and outcomes. Objective To quantify the societal burden of IRDs in Belgium in 2023 Methods This cost-of-illness study estimated the total costs of the 11 most prevalent IRDs in Belgium. A survey of Belgian IRD patients collected primary data on disease burden, health resource utilization, productivity, and care-related expenses. Additionally, data on prevalence and health system costs were based on a literature review from PubMed and the Cochrane Library. Results Patients reported a substantial impact on daily activities (96%), mental health (81%), and 78% reported having received genetic testing. IRDs impose a significant economic burden in Belgium, with an average annual cost of €37,228 per patient and a total cumulative burden of €129.4 million. Indirect non-healthcare costs represented the largest proportion (84%), followed by direct healthcare costs (12%), mainly from rehabilitation, and direct non-healthcare costs (4%). Indirect costs included significant productivity losses of €77.7 million and an informal care burden of €31.3 million. Government support programmes accounted for €4.9 million annually. Conclusion This study highlights the substantial clinical and economic burden of IRDs on Belgian society. Therefore, it is important to continue investing in research and development, as well as to consider the substantial societal impact of these conditions in decision-making and shaping policy changes for Belgium. Future investments informed by these findings can contribute to decreasing the burden on society and enhance the well-being, inclusion and productivity of patients and caregivers.